VD_FINDINFO HC / 2015 / 222 vom 9. März 2015 - VD Tribunal cantonal (2015)
AVANCE DE FRAIS, ASSURANCE-MALADIE ET ACCIDENTS, ASSURANCE COMPLÉMENTAIRE | 103 CPC (CH), 113 al. 2 let. f CPC (CH), 319 CPC (CH), 319 let. b ch. 1 CPC (CH), 319 let. b CPC (CH), 320 CPC (CH), 321 al. 1 CPC (CH), 321 CPC (CH)